Pengaruh Kombinasi Populasi Tumpangsari Kedelai-Singkong pada Pertumbuhan dan Hasil Benih Tanaman Kedelai dan Hasil Umbi Singkong - Pramono, Eko; Manik, Tumiar Katarina B.; Hadi, Muhammad Syamsoel; Salsabila, Erika Fadia (JURNAL AGROTROPIKA, 2024)
Intercropping soybeans with cassava can become one solution to increase the production of soybean in Indonesia. This research aimed to determine the most optimal population combination of soybean-cassava intercropping for the growth and yield of soybean seeds, cassava tuber yield, and land use efficiency (LUE)..  The research was carried out on the farm land of the Main Seed Center in Sekincau District, West Lampung Regency, Lampung Province, Indonesia at -5°02’27” South and 104°18’16” East at elevation of 1173.1 meter from sea level and at the Seed and Plant Breeding Laboratory Faculty of Agriculture University of Lampung during June 2022 - February 2023. The four treatments of population combination of soybean-cassava intercropping were applied in a completely randomized block design (CRBD) and replicated five times in five blocks. The four population combination treatments of soybean-cassava intercropping were a) 100% soybean and 0% cassava (monoculture) (p₁), b) 67% soybean and 97% cassava (p₂), c) 67% soybean and 89% cassava (p₃), and d) 50% soybeans and 97% cassava (p₄). The growth and the seed yield per soybean stem of monoculture did not differ to those of the soybean-cassava intercropping, but the soybean seed yield per plot area of the intercropping was lower than those of monoculture. Its mainly due to the soybean population of the intercropping was lower compared to monoculture. All population combinations in soybean-cassava intercropping were effective in supporting the growth and yield of soybean seeds, but the population combination of 50% soybean and 97% cassava (p₄) was also effective in supporting cassava tuber yield, and had the highest land use efficiency among other population combinations. Key words:  flowering age, plant height, seed weight, tuber weight of cassava